Ocular pulse amplitude (OPA) in canine ADAMTS10-open-angle glaucoma (ADAMTS10-OAG) - Raphtis, Vanessa A.; Sharma, Dhruv; Wang, Sichao; Kim, Jae Y.; Jacobson, Amanda L.; Harman, Christine D.; Komáromy, András M. (Frontiers in Bioengineering and Biotechnology, 2023)
The role of ocular rigidity and biomechanics remains incompletely understood in glaucoma, including assessing an individual’s sensitivity to intraocular pressure (IOP). In this regard, the clinical assessment of ocular biomechanics represents an important need. The purpose of this study was to determine a possible relationship between the G661R missense mutation in the ADAMTS10 gene and the ocular pulse amplitude (OPA), the difference between diastolic and systolic intraocular pressure (IOP), in a well-established canine model of open-angle glaucoma (OAG). Animals studied included 39 ADAMTS10-mutant dogs with different stages of OAG and 14 unaffected control male and female dogs between 6 months and 12 years (median: 3.2 years). Dogs were sedated intravenously with butorphanol tartrate and midazolam HCl, and their IOPs were measured with the Icare® Tonovet rebound tonometer. The Reichert Model 30™ Pneumotonometer was used to measure OPA. Central corneal thickness (CCT) was measured via Accutome® PachPen, and A-scan biometry was assessed with DGH Technology Scanmate. All outcome measures of left and right eyes were averaged for each dog. Data analysis was conducted with ANOVA, ANCOVA, and regression models. ADAMTS10-OAG-affected dogs displayed a greater IOP of 23.0 ± 7.0 mmHg (mean ± SD) compared to 15.3 ± 3.6 mmHg in normal dogs (p < 0.0001). Mutant dogs had a significantly lower OPA of 4.1 ± 2.0 mmHg compared to 6.5 ± 2.8 mmHg of normal dogs (p < 0.01). There was no significant age effect, but OPA was correlated with IOP in ADAMTS10-mutant dogs. The lower OPA in ADAMTS10-mutant dogs corresponds to the previously documented weaker and biochemically distinct posterior sclera, but a direct relationship remains to be confirmed. The OPA may be a valuable clinical tool to assess ocular stiffness and an individual’s susceptibility to IOP elevation.